Analysis of the Use of Artificial Intelligence in Preparing Regional Government Financial Reports - Nasution, Dito Aditia Darma (Universitas 17 Agustus 1945 Semarang, 2024)
The use of artificial intelligence is projected to have a significant impact on the preparation of regional government financial reports, especially in terms of reliability and efficiency. This research aims to analyze the use of AI in preparing regional government financial reports which was previously carried out conventionally and the challenges faced by regional governments in adopting it. This research uses a literature study method to identify trends and findings related to the use of AI in regional financial accounting. The research results show that AI is able to increase efficiency and reliability, although there are challenges in its application, such as the need to adapt and improve the quality of human resources and vulnerabilities in financial data security.